2001
DOI: 10.1002/1521-186x(200102)22:2<71::aid-bem1008>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency electromagnetic fields and heat shock can increase microvesicle motility in astrocytes

Abstract: The effect of extremely low frequency electromagnetic fields (EMF) on microvesicles was examined in rat astrocytes by video-enhanced microscopy in combination with a perfusable cell chamber. The EMF effect was compared with the effect of heat shock (HS) and with a combination of them both. The velocity of microvesicles was measured using image processing software (NIH Scion image 1.61). After exposure of astrocytes to EMF (50 Hz, 100microT, 1 h), the velocity of microvesicles in astrocytes increased from 0.32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Primary rat astrocytes were treated at 45°C for 10 min before 50 Hz MF exposure for 1 h at 100 µT. Increase in the microvesicle velocity was detected after both MF exposure and heat treatment alone, which was not modified by the combined treatments ( 72 ).…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Primary rat astrocytes were treated at 45°C for 10 min before 50 Hz MF exposure for 1 h at 100 µT. Increase in the microvesicle velocity was detected after both MF exposure and heat treatment alone, which was not modified by the combined treatments ( 72 ).…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…At the cellular level, ELF MFs, as well as heat shock, proved to increase microvescicle motility in astrocytes (Golfert et al 2001). It was observed that both sedimentation and aggregation of erythrocytes were MF-dependent (Lino and Okuda 2001).…”
Section: Introductionmentioning
confidence: 70%
“…At the cellular level, an MF-dependence of the membrane state was established through cytofluorimetry [81]. ELF MFs, as well as heat shock, proved to increase microvescicle motility in astrocytes [82]. Both sedimentation and aggregation of erythrocytes were MF-dependent [83].…”
Section: Biotargets Of Middle Complexity Exhibited a Moderate Mf-stabmentioning
confidence: 99%